Analisis Hubungan Spread Of Interest Rate, Fee Based Income, dan Loan To Deposit Terhadap Tingkat Return On Assets (Roa) (Studi Pada BUMN Perbankan yang Terdaftar di Bursa Efek Indonesia) - Hendriyati Haryani; Warseno Warseno (UNIVERSITAS RAHARJA, 2022)
The aim of this study is: (1) To determine the relationship of interest rate spreads on the level of return on assets of gov owned bank that listed in Indonesia Stock Exchanges. (2) To determine the relationship of fee-based income to the level of return on assets of gov owned bank that listed in Indonesia Stock Exchanges. (3) To determine the relationship of loan to deposit ratio of the rate of return on assets of gov owned bank that listed in Indonesia Stock Exchanges. (4) To determine the relationship of interest rate spreads, fee-based income, and loan-to-deposit ratio of the rate of return on assets together of gov owned bank that listed in Indonesia Stock Exchanges. The method used in this research is descriptive kuantitative. The results of the study partially fee-based income has no significant effect on return on assets, the spread of the interest rate has a significant effect on return on assets, loan to deposit ratio has no significant effect on return on assets, and together spread of interest rate, fee-based income, and loan-to-deposit ratio has a significant influence on the Return on Assets (ROA) of gov owned bank that listed in Indonesia Stock Exchanges